Involvement of palms and soles in patients with autoimmune bullous diseases: a comparative analysis of a diagnostically relevant localization - Magdalena Jałowska; Maciej Spałek; Monika Bowszyc-Dmochowska; Justyna Gornowicz- Porowska; Marian Dmochowski (Frontiers in Immunology, 2023)
IntroductionThe involvement of palms and soles is variable among disease entities belonging to autoimmune bullous diseases (AIBD). We present our own clinical-laboratory experience concerning presentations of skin lesions on palms and soles in the pemphigus diseases group, pemphigoid diseases group, epidermolysis bullosa acquisita (EBA), and lichen planus pemphigoides (LPP) and discuss the pertinent literature.MethodsLesions on palms and soles were assessed retrospectively on the basis of just photographic archives from the beginning of 2014 to March 2023. We comparatively evaluated 462 Slavic patients with AIBD.ResultsPalmoplantar involvement was observed in only 21 patients with AIBD (12 females and 9 males). There was no statistically significant difference between palmoplantar involvement in the pemphigus diseases group compared to the pemphigoid diseases group and no statistically significant difference between the pemphigus diseases group compared to the subepithelial AIBD.DiscussionNevertheless, particularly in LPP and EBA, and occasionally in pemphigus diseases and pemphigoid diseases groups of AIBD, localization on palms and soles may be diagnostically important at the clinical level.